Studies on Ottoman science and culture - İhsanoğlu, Ekmeleddin, author.
1 online resource (xi, 349 pages)
Keywords: “Studies on Ottoman Science and Culture brings together eleven articles by distinguished historian Ekmeleddin İhsanoğlu. The book addresses multiple issues related to the histories of science and culture during the Ottoman era. Most of the articles contained in this volume were the first contributions to their respective topics, and they continue to provoke discussion and debate amongst academics to this day. The first volume of the author's collected papers that appeared in the Variorum Collected Studies (2004) dispelled the negative opinions towards Ottoman science asserted by scholars of the previous generation. In this new volume, the author continues to explore and develop the paradigm of scientific activities and cultural interactions both within and beyond the Ottoman Empire. One of the topics examined is the attitude of Islamic scholars towards revolutionary notions in Western science, including Copernican heliocentrism and Darwin's theory of evolution. This book will appeal to scholars and students of Ottoman history, as well as those interested in the history of science and cultural history“--